Transition from viscoelastic to fracture-like peeling of pressure-sensitive adhesives. Issue 5 (11th January 2022) - Grzelka, Marion; Kooij, Stefan; Woutersen, Sander; Adda-Bedia, Mokhtar; Bonn, Daniel
Abstract : We investigate the peeling of a pressure-sensitive adhesive under different environmental conditions. Applying 'time–humidity' superposition, we quantitatively explain the correlation between the peeling velocity and the relative humidity. Abstract : We investigate the process of the slow unrolling of a roll of typical pressure-sensitive adhesive, Scotch tape, under its own weight. Probing the peeling velocities down to nm s −1 resolution, which is three orders of magnitudes lower than earlier measurements, we find that the speed is still non-zero. Moreover, the velocity is correlated to the relative humidity. A humidity increase leads to water uptake, making the adhesive weaker and easier to peel. At very low humidity, the adhesive becomes so stiff that it mainly responds elastically, leading to a peeling process akin to interfacial fracture. We provide a quantitative understanding of the peeling velocity in the two regimes.